Faktor yang Memengaruhi Keputusan Pembelian Kosmetik Halal - Shinta Marbella Christine; Tita Nursyamsiah; Qoriatul Hasanah (Tazkia Islamic Finance and Business Review, 2022)
Muslims are required to consume halal products. One of the halal products consumed by Muslims is cosmetics. Based on the Zap Beauty Index (2020) survey, it was found that 49.5 percent of consumers did not pay attention to halal labels when buying cosmetics. This study aims to analyze the determinant factors of purchase intention of halal cosmetics in Bogor Regency by taking a sample of 100 respondents. The sampling method was purposive-sampling and analyzed using Structural Equation Model-Partial Least Square (SEM-PLS). The results show that the factors that significantly determine purchase intention in Bogor Regency to buy halal cosmetics are attitude, subjective norm, halal awareness, and religiosity. Keywords: Halal, Cosmetics, Purchase intention, SEM-PLS